ANALISIS PROGRAM PEMBANGUNAN DESA WISATA WONOLOPO DI KOTA SEMARANG - Rezza Abdy Pradana; Warsito . .; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2017)
DEVELOPMENT PROGRAM ANALYSIS OF WONOLOPO TOURIST VILLAGE IN SEMARANG CITYREZZA ABDY PRADANA(GOVERNMENT SCIENCE, FISIP UNDIP, SEMARANG)ABSTRACTIONThis research was motivated by the Tourism Village Wonolopo in Semarang who can not develop like other tourist village in the city of Semarang. So the tourist village in the Village program Wonolopo threatened not to proceed. Wonolopo Tourism Village Development Program should be maintained to create a prosperous society and independent evenly according to the Indonesian government program that people want mensejahterkan evenly from the Central State to the people in the village and prepare people to face the free market in ASEAN. To maintain Wonolopo Tourism Village, Semarang city government should be able to develop tourism village Wonolopo. Semarang city government should establish cooperation with Tourism Awareness Group Wonolopo and Tourism Village community in managing the program Wonolopo tourist village in Sub Wonolopo.This type of research is descriptive analysis with qualitative approach. Sources of data derived from primary data through interviews with key informants or person with semistructure interview techniques. Secondary data derived from the data of documents, archives and other sources related to the research. Data collection techniques in this study using interviews, observation and documentation. While the analytical techniques used in this research by analyzing qualitative data analysis in the form of a description or notes, depictions and conclusion on the symptoms studied.The results of this study found that the program is not developed tourist villages in the Village Wonolopo there are problems that are diinternal Wonolopo Travel Awareness Group itself. The problems started with the improper management of funds acquired through PNPM assistance of the Central Government by one group of people in the Travel Awareness Group. Additionally, adannya supervision less than Department of Culture and Tourism of Semarang on Wonolopo Travel Awareness Group. Moreover, the lack of attention from the local government of Semarang look at the lack of supporting facilities for running programs Wonolopo Tourism Village. Road infrastructure is still a lot of damage and there are no signposts direction. So that the revamping of the base is necessary for Rural Development Program in Semarang Tourism Wonolopo could run better than beforeKeywords: Rural Development Wonolopo Travel, Tourism Awareness Group Wonolopo, Tourism Village Wonolopo Semarang